Function of Akkermansia muciniphila in Obesity: Interactions With Lipid Metabolism, Immune Response and Gut Systems - Xu, Yu; Wang, Ning; Tan, Hor-Yue; Li, Sha; Zhang, Cheng; Feng, Yibin (Frontiers in Microbiology, 2020)
Obesity and its metabolic syndrome, including liver disorders and type 2 diabetes, are a worldwide epidemic and intimately linked to diet. The gut microbiota interaction has been pointed out as a hot topic research at treating obesity and related metabolic diseases by influencing energy metabolism and immune system. In terms of the novel identified beneficial microbes, Akkermansia muciniphila (A.muciniphila ) is colonized in the mucosa layer of the gut and modulates basal metabolism. A.muciniphila is consistently correlated with obesity. The causal beneficial impact on A.muciniphila-treated obesity is coming to light, which is proved by a variety of animal models and human studies. A.muciniphila has been characterized as a beneficial player in body metabolism and create a great expectation for treatments of the metabolic disorders associated with obesity, as well as considered as new generation therapeutic agents. This paper aimed to was to investigate the underlying basic mechanism of A.muciniphila-related obesity and host interactions in recent discoveries, facilitating to establish the causal relationship in human and the A.muciniphila-associated therapeutic supplement.